The Psycho-Bio-Physical Nature of Man, Possibility and Technology of Their Extended Mind - Monserrat, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The facts and inferences exposed in this writing, and the arguments that support it, allow us to conclude that the «extension of the mind», opened during the evolutionary process, since always and today accelerated by the work of human intervention, in no case authorizes us to consider that the «extension of mind» has changed human nature, as we have always known it. Therefore, there is no justification to speak of transhumanism, as if a new man, a «transhuman», had appeared at the moment of the Singularity, whose nature had undergone substantial changes in relation to the usual human nature. For this reason, we consider that we should continue speaking of an «extensive humanism». No more.